The good and the bad faces of STAT1 in solid tumours. (January 2017) - Meissl, Katrin; Macho-Maschler, Sabine; Müller, Mathias; Strobl, Birgit
Abstract: Signal transducer and activator of transcription (STAT) 1 is part of the Janus kinase (JAK)/STAT signalling cascade and is best known for its essential role in mediating responses to all types of interferons (IFN). STAT1 regulates a variety of cellular processes, such as antimicrobial activities, cell proliferation and cell death. It exerts important immune modulatory activities both in the innate and the adaptive arm of the immune system. Based on studies in mice and data from human patients, STAT1 is generally considered a tumour suppressor but there is growing evidence that it can also act as a tumour promoter. This review aims at contrasting the two faces of STAT1 in tumourigenesis and providing an overview on the current knowledge of the underlying mechanisms or pathways.